(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
IEEE 802.11n amendment is currently the most effective solution within the range of Wireless Local Area Networks (LAN). The standard provides many enhancements and is improved upon in many ways. One of the main goals of these improvements is to get high performance of Throughput and less delay of the MAC layer. The main objective of this research is to evaluate the performance of very high-speed WLANs (IEEE 802.11n) in terms of the aggregation method. IEEE 802.11n is intended to support frame aggregation which combines the packets into a large frame called (A-MSDU) aggregation MAC services data unit and aggregates the frames into a large frame called (A-MPDU) Aggregation MAC protocol data unit, which are the two key performance features are the ability to enhance the transmission overheads in MAC layer over a noisy channel. The system is examined by simulation using NS-2.34. The simulation results show that the proposed schemes significantly improve the performance over distributed coordination function (DCF) and the A-MSDU method significantly improves the performance of throughput over the literature scheme up to 103.16% while the A-MPDU method improves the performance of throughput over the literature scheme up to 155.15%. In conclusion, this research has achieved its stated objective of evaluating the performance of very high-speed WLANs (IEEE 802.11n) in terms of the aggregation method. Additionally, the proposed schemes show a significant improvement compared with a literature scheme.